Emergência e análise ultraestrutural de plântulas de soja inoculadas com Sclerotinia sclerotiorum sob efeito da aplicação de Trichoderma harzianum - Silva, Fabiano França Da; Castro, Elisa De Melo; Moreira, Silvino Intra; Ferreira, Thiago Costa [UNESP]; Lima, Amador Eduardo De; Alves, Eduardo (Grupo Paulista de Fitopatologia, 2017)
The high susceptibility of soybean to white mold has negatively impacted its productivity. Currently, biological control methods, such as the use of Trichoderma spp., have provided alternatives to chemical control, as they promote less environmental impact and favor the plant growth. The aim of this study was to evaluate the effects of T. harzianum on the emergence of soybean seeds inoculated with Sclerotinia sclerotiorum, besides identifying the interaction between fungi and soybeans by means of scanning electron microscopy (SEM). Soybean seeds were subjected to the following treatments: 1. Without S. sclerotiorum, in PDA+Mannitol; 2. With S. sclerotiorum, in PDA+Mannitol; 3. With Ecotrich®WP and without S. sclerotiorum, in PDA+Mannitol; 4. With S. sclerotiorum and Ecotrich® WP, in PDA+Mannitol. The emergence test was conducted on trays with sterile sand at 25 °C for 8 days. Then, the vegetative organs of emerged seedlings were sectioned to evaluate, by scanning electron microscopy (SEM), T. harzianum potential to parasitize and inhibit S. sclerotiorum. In fact, the white mold is capable of colonizing and deteriorating all soybean seeds. T. harzianum is effective in colonizing the root system of soybeans but does not contribute to emergence, compared to control. Based on the ultrastructural analysis, mycoparasitism of T. harzianum and S. Sclerotiorum was evidenced, but the control of the causal agent of white mold was not as effective as shown in other studies.

A elevada susceptibilidade da soja ao mofo-branco tem impactado negativamente a sua produtividade. Atualmente métodos de controle biológico como o uso de Trichoderma spp. têm proporcionado alternativas ao controle químico, com menor impacto ambiental e favorecimento do desenvolvimento vegetal. Objetivou-se avaliar os efeitos de T. harzianum sobre a emergência de sementes de soja inoculadas com Sclerotinia sclerotiorum; além de verificar a interação entre os fungos e com a soja, por meio da microscopia eletrônica de varredura (MEV). Sementes de soja foram submetidas aos tratamentos: 1. Sem S. sclerotiorum, em BDA+Manitol; 2. Com S. sclerotiorum, em BDA+Manitol; 3. Com Ecotrich®WP e sem S. sclerotiorum, em BDA+Manitol; 4. Com S. sclerotiorum e Ecotrich® WP, em BDA+Manitol. O teste de emergência foi conduzido em bandejas com areia esterilizada a 25 ºC por 8 dias. Após isto foram seccionados órgãos vegetativos das plântulas emergidas para avaliar, por meio da Microscopia Eletrônica de Varredura (MEV), o potencial de T. harzianum em parasitar e inibir S. sclerotiorum. De fato, o mofo-branco é capaz de colonizar e deteriorar todas as sementes de soja. T. harzianum mostra-se efetivo em colonizar o sistema radicular da soja, porém não contribui para a emergência quando comparada com a testemunha. A análise ultraestrutural permitiu evidenciar o micoparasitismo de T. harzianum a S. sclerotiorum, porém o controle do agente causal do mofo-branco não foi efetivo quanto se mostrou em outros estudos.
Emergence and ultrastructural analysis of soybean seedlings inoculated with Sclerotinia sclerotiorum under the effect of Trichoderma harzianum application
Keywords: Biological control; Glycine max; White mold; Scanning Electron Microscopy; Controle biológico; Glycine max; Mofo-branco; Microscopia Eletrônica de Varredura